Local community readiness and willingness to conservation of peat swamp forest in Air Hitam Muar. - Azli, Aina farahin; Sawari, Siti Salwa (2019)
Peat swamp forest (PSF) has high potential in delivering wide range of economic and social benefits through developing ecotourism to conservation. However it is rarely to be optimised due to poor performance and involvement of locals as they are been viewed to simply gain benefits from tourism development rather than having cooperation in the process of achieving such development. Less awareness due to lack of knowledge and skills by the locals were also contributed to unwell management of natural resources. Therefore, this paper aimed to investigate the readiness and willingness of local community to participate in conserving PSF in Ayer Hitam Johor. In such, it is vital for natural resources to be well managed purposely to maximise the benefits, minimise the cost and reduce negative impacts resulted from conservation as well as achieving successful Community based conservation (CBC) in Ayer Hitam Muar. This study is quantitative nature. It was carried out by conducting survey around 30 respondents who living in adjacent to Ayer Hitam PSF. The data was analysed by using IBM statistical package for social science (SPSS) version 21 through several analysis such as descriptive analysis, descriptive analysis and reliability analysis. The outcomes of the research shows that majority of local community were received both direct and indirect benefits which influence the local community to participate in protect the peat swamp forest. In addition to this, the result shows that most of the locals acknowledged on the issues and current situation of the peat swamp forest, however few of them were not physically ready and willing to contribute in conservation due to age factor. The major contribution that can be seen is the local participation can lead toward developing tourism attraction on peat swamp forest in sustainability way through establishing Community based Conservation which able to protect the environment.